Remarques sur la négation connexionnelle en occitan languedocien - Floricic, Franck (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2006)
The aim of this paper is to offer a description of sentence negation in the Languedocian variety of Occitan. After a brief overview of the general properties of negation in Occitan, it will be shown, on the basis of unpublished dialectological data gathered in the 60's and 70's, that in some localities within the Occitan area the negative marker pas has cliticized. However, gapping structures show that in the dialects in which pas has acquired clitic status, it is still possible to use the tonic form, thus pointing to the conclusion that in these dialects sentence negation has two allomorphs. The last part of the paper deals with cliticization as a general phenomenon, and questions Witold Manczak's view according to which there is no basis for a distinction between tonic and atonic forms. The problem of frequency will be discussed, and it will be argued that the cliticization phenomena presented in this paper should not be analyzed as a consequence of this factor.
Remarks on the connective negation in Languedocian variety of Occitan